2018
DOI: 10.1016/j.jesf.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of jaw clenching wearing customized mouthguards on agility, power and vertical jump in male high-standard basketball players

Abstract: Background/ObjectiveBasketball players commonly use mouthguards for protecting their mouths from collisions with other players. Besides, literature reports that specific types of mouthguards may become an ergogenic device that facilitates a powerful jaw clenching, and a subsequent concurrent activation potentiation through this remote voluntary contraction of the mandible muscles.MethodsA randomized within-subjects design was used to study the effects of this mechanism on muscular performance (vertical jump, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 46 publications
0
49
1
Order By: Relevance
“…The present study focused on individually customized MGs, which are more comfortable and have a better fit compared to selfadapting MGs [18,21,22]. Some studies observed improved peripheral biomechanical control due to the influence of custom made MGs [11,12,[23][24][25][26]. Various independent studies claim that customized MGs have beneficial effects with regard to aerobic energy supply, with significant improvements in mean power, peak power, and time to peak power, when assessed with a 30 s Wingate Anaerobic Test when wearing an individually custom made MG [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study focused on individually customized MGs, which are more comfortable and have a better fit compared to selfadapting MGs [18,21,22]. Some studies observed improved peripheral biomechanical control due to the influence of custom made MGs [11,12,[23][24][25][26]. Various independent studies claim that customized MGs have beneficial effects with regard to aerobic energy supply, with significant improvements in mean power, peak power, and time to peak power, when assessed with a 30 s Wingate Anaerobic Test when wearing an individually custom made MG [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Various independent studies claim that customized MGs have beneficial effects with regard to aerobic energy supply, with significant improvements in mean power, peak power, and time to peak power, when assessed with a 30 s Wingate Anaerobic Test when wearing an individually custom made MG [24,25]. These studies indicate that custom made MGs are superior to either no MG or self-adapted MGs [11,12,19,20,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…21,25 It has been reported that wearing an occlusal splint or a mouthguard with balanced occlusion can improve athletic performance by increasing muscle strength and achieving a more balanced body posture. 14,26,27 However, other studies have found that wearing an occlusal-balanced appliance does not affect posture, muscle activity, or athletic performance, 28,29 resulting in this feature having unclear benefits. 16 Most mouthguards are fabricated without this occlusal accommodation, partly due to the higher costs of clinical and laboratory preparation, 23 so there is a need to assess the cost-benefit relationship of occlusal-accommodated mouthguards before advocating their widespread use to prevent orofacial injury.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a mouthguard may have positive effects on neuromuscular chains. A mouthguard may facilitate powerful jaw clenching and a subsequent concurrent activation potentiation through a remote voluntary contraction of the mandible muscles 2 7 12 . Remote voluntary contractions are a muscle action of the prime mover while performing a simultaneous muscle action with another part of the body 12 .…”
Section: Introductionmentioning
confidence: 99%